The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1158/0008-5472.can-07-3069
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Lethality by Lentiviral Short Hairpin RNA Silencing of Thymidylate Kinase and Doxorubicin in Colon Cancer Cells Regardless of the p53 Status

Abstract: Intracellular supply of dTTP is a highly regulated process and has been a key target for chemotherapeutic drug development. Thymidylate kinase (TMPK) is the key enzyme for dTTP formation in both de novo and salvage pathways. In this study, we used lentiviral-based small hairpin RNA to silence TMPK expression in p53(+/+) and p53(À/À) HCT-116 colon cancer cells. This approach was sufficient to decrease the dTTP pool gradually without affecting p53 expression and generating cytotoxicity. TMPK knockdown significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…[25] However, in another study, repression of the TYMK gene by RNAi did not induce direct lethal consequences in human colon cancer cell lines. [20] Quantitative PCR results revealed that silencing of the TYMK gene by RNAi achieved a significant (P < 0.02) 4-fold reduction of TYMK expression in the tymk-shRNA cell lines compared to the value of control cell lines ( Figure 4A). To determine whether this reduction had any effect on expression levels of DUT, TK, DCTD, and TYMS genes, quantitative PCR measurements were performed to measure their mRNA levels in tymk-shRNA cells.…”
Section: Silencing Of the Tymk Gene And Its Effect On Expressions Of mentioning
confidence: 95%
See 1 more Smart Citation
“…[25] However, in another study, repression of the TYMK gene by RNAi did not induce direct lethal consequences in human colon cancer cell lines. [20] Quantitative PCR results revealed that silencing of the TYMK gene by RNAi achieved a significant (P < 0.02) 4-fold reduction of TYMK expression in the tymk-shRNA cell lines compared to the value of control cell lines ( Figure 4A). To determine whether this reduction had any effect on expression levels of DUT, TK, DCTD, and TYMS genes, quantitative PCR measurements were performed to measure their mRNA levels in tymk-shRNA cells.…”
Section: Silencing Of the Tymk Gene And Its Effect On Expressions Of mentioning
confidence: 95%
“…[5,18,19] Efficient RNAi experiments were also reported to silence the TYMK and TYMS genes in colon cancer cell lines. [20] In the present study, we aimed at generation of stable HeLa cell lines in which either the DUT or the TYMK gene is constantly silenced by a vector-based RNAi system. With respect to the essential functions of the aforementioned enzymes in thymidylate metabolism, we aimed to characterize the gene expression pattern of DUT, TK, TYMK, DCTD, and TYMS enzymes as molecular responses to the gene silencing (cf.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that reducing the cellular level of dTTP by silencing thymidylate kinase expression significantly sensitizes tumor cells to a chemotherapeutic agent, demonstrating the importance of dTTP supply in tumor cell survival after genotoxic insults (39). Importantly, blocking TS does not necessarily lead to chemosensitization unless thymidine is deprived from the culture medium (39). These findings prompt us to further investigate the functional contribution of TK1-mediated dTTP synthesis in DNA damage response.…”
mentioning
confidence: 97%
“…A number of studies have shown that the decrease in the dTTP level due to TK deficiency is correlated with the increase in DNA damage-in-duced cell death and mutagenesis (33)(34)(35)(36)(37)(38). It was previously shown that reducing the cellular level of dTTP by silencing thymidylate kinase expression significantly sensitizes tumor cells to a chemotherapeutic agent, demonstrating the importance of dTTP supply in tumor cell survival after genotoxic insults (39). Importantly, blocking TS does not necessarily lead to chemosensitization unless thymidine is deprived from the culture medium (39).…”
mentioning
confidence: 99%
“…We have previously deciphered, at least partly, how ISP induces apoptosis in the human HCT-116 colon cancer cells (9), which displays sensitivity to pro-apoptotic stimuli (24,25). ISP induces apoptosis in HCT-116 colon cancer cells as shown by the translocation of phosphatidylserine from the inner layer to the outer layer of the plasma membrane, chromatin condensation, DNA fragmentation, and caspase-3 and -9 activation (9).…”
Section: Discussionmentioning
confidence: 99%